Perceptions and Experiences of Nursing Students in Caring for People Living with HIV/AIDS in South Africa: A Qualitative Study - Mabhiza, Ruwadzano Dorcas; Bhana, Varshika; Sedibe, Heather (Nurse Media Journal of Nursing, 2024)
Background: Although previous studies focusing on nurses’ perceptions of caring for people living with HIV (PLHIV) have been conducted in numerous countries, little is known about first-year student nurses’ perceptions and experiences regarding their role in caring for PLHIV in South Africa. To ensure quality care for PLHIV, it is essential to explore first-year student nurses’ roles in caring for PLHIV.Purpose: This study aimed to explore the perceptions and experiences of first-year nursing students on their role in caring for PLHIV in South Africa.Methods: A qualitative exploratory descriptive design was employed for this study, utilizing a purposive sampling method to recruit 18 participants. These participants were first-year nursing students aged 18 or older, enrolled in a 4-year bachelor’s degree nursing program, and who had completed clinical placements in hospitals. Data collection involved two focus group discussions (FGDs), one comprising eight participants and the other ten participants. Thematic analysis was employed to analyze the collected data.Results: Four main themes were drawn from two FGDs, including (1) students’ unpreparedness in their role to care for PLHIV, (2) disclosure practices and student safety concerns, (3) personal backgrounds and attitudes towards PLHIV care, and (4) physical and psychological wellbeing of students while caring for PLHIV. Furthermore, 11 sub-themes were subsequently drawn from these main themes. Thematic sub-themes and individual focus group responses were relied on to reach data saturation despite the small number of FGD sessions.Conclusion: First-year nursing students had negative and positive perceptions and experiences when caring for PLHIV. There is a need for these students to acquire adequate theoretical knowledge and practical skills to enhance clinical preparation for their role in clinical facilities. This could improve their perceptions regarding caring for PLHIV in the clinical setting and result in improved care.